Chronic fecal impaction in the megarectosigmoid. Therapeutic behavior. - Canessa, César; Gómez del Valle, María José; Caraballo, Mónica (Cirugía del Uruguay, 2002)
Seven patients with megarectumsigma underwent surgery for chronic faecal impaction, reviewing clinical diagnosis, aetiology and medica! and surgical management. It is suggested medica! management of chronic faecal impaction trying to achieve elective surgery. The curative surgery should include the resection of all pathologic bowel, but in Duhamel procedure and its modifications distal rectal transection should be at the peritoneal reflection. HabrGama modification has shown to be technically easier and it has been communicated good functional results. Local unfavourable conditions may be resol ve by staged surgery, which allows outline definitive bowel reconstruction after functional assessment